Therapeutic Effects of Fenugreek Seeds on Diabetic Rabbits - Anees Abbas Yaseen Al-Fatlawi; Atheer Abbas Yaseen Al-Fatlawi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The aim of this study was to investigate the therapeutic effects of Fenugreek on rabbit with diabetes inducedexperimentally. A total of thirty rabbits were divided into 3 groups, each group contain 10 animals, G1(control negative), G2 (Control positive), G3 induced diabetes by giving alloxan 135mg/kg IP then after2 weeks of diabetes induction, animals were drenched with Fenugreek seeds 100mg/kg orally. The resultsshowed that rabbits in G2 suffered from hypoglycemia due to Fenugreek effects as compared with G1group, also, G3 showed a significant gradual decrease in glucose levels especially after 96hrs of giving theFenugreek. In conclusion, Fenugreek showed a therapeutic effect as anti-diabetic in rabbits.